Managerial Ownership's Impact on Tech Firms' Financial Distress Risk: Dampak Kepemilikan Manajerial terhadap Risiko Kesulitan Keuangan Perusahaan Teknologi - Fachrul A Siregar; Meiko Andreas; Iskandar Muda; Noor Marini Haji Abdullah (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to examine how profitability and leverage influence the likelihood of financial distress among technology companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024, and whether managerial ownership moderates these relationships. Using a quantitative research design with 102 firm-year observations, panel data regression analysis was employed to test the hypotheses. The results show that higher profitability significantly reduces the risk of financial distress, while higher leverage increases it. Notably, managerial ownership strengthens both of these relationships—intensifying the protective effect of profitability and exacerbating the risk-enhancing effect of leverage. These findings suggest that while profitability supports financial stability, excessive debt remains a critical risk factor, and managerial ownership plays a dual role that can amplify both positive and negative outcomes. This highlights the importance of balanced financial policies and effective corporate governance in navigating the volatile, innovation-driven technology sector.